2017
DOI: 10.1007/s12020-017-1439-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonfunctioning adrenal incidentaloma affecting central blood pressure and arterial stiffness parameters

Abstract: NFAIs are known as cardiometabolically innocent, but in our study, both peripheral and central blood pressure values and arterial stiffness parameters were negatively affected in patients diagnosed with NFAI who have no traditional cardiovascular risk factors. These patients are at risk of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Finally, some recent reports suggested that patients with NFA may also carry an increased CV risk compared with the general population, thus our study may underestimate the magnitude of cardiac damage associated with pACS. Among the hypotheses proposed, there is the possibility that NFAs produce excess cortisol in a cyclic manner, or during stress, or release excess steroid precursors, such as deoxycorticosterone and corticosterone (6,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some recent reports suggested that patients with NFA may also carry an increased CV risk compared with the general population, thus our study may underestimate the magnitude of cardiac damage associated with pACS. Among the hypotheses proposed, there is the possibility that NFAs produce excess cortisol in a cyclic manner, or during stress, or release excess steroid precursors, such as deoxycorticosterone and corticosterone (6,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Many invasive, noninvasive methods and scoring systems are currently used for predicting CVDs. Arterial stiffness is also considered an independent risk indicator for cardiovascular diseases (3)(4)(5). Increased stiffness in central arteries leads to undesired hemodynamic consequences such as the expansion of pulse pressure (PP) and increased flow to microcirculation.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 2 we summarize all publications included in our review. In the investigated groups of AI patients an increased CIMT was observed, illustrating morphological changes in carotid arteries expressed by intimal hyperplasia and endothelial atherosclerosis, as well as increased PWV or AIx that are the indicators of arterial stiffness [54,55,[58][59][60]63,64]. Endothelial dysfunction in the form of FMD was also observed [55].…”
Section: Final Assessment Of the Available Cvd Markers In Patients Wimentioning
confidence: 77%
“…Similar conclusions were drawn by Akkan T. et al who observed higher PWV and AIx adjusted for heart rate in NFAI patients. Authors have observed a negative correlation between PWV and 24-h urinary free cortisol levels [63]. In the study of Sbardella E. et al significantly higher PWV in pACS patients was confirmed [64].…”
Section: Arterial Stiffness Indexmentioning
confidence: 89%